Family-Based Reintegration : Effective Interventions for Juveniles on Parole. - Rowland, Marcy K. (Criminal justice (LFB Scholarly Publishing LLC), 2009)
In 2002, a family-based approach to parole (Functional Family Parole), was implemented across the state of Washington. Rowland compares the behavioral and family functioning outcomes of youth who received the intervention with a matched control group of youth who received traditional parole. She finds that, without consideration of model adherence, the FFP and control groups did not differ in overall recidivism. However, when implemented with high model adherence, FFP achieved a 14.6% reduction in felony recidivism compared to traditional parole. As adherence to the FFP model increases, there.